Towards the dynamics of trust in the relationship between project-based firms and suppliers - Xu, Jing; Smyth, Hedley; Zerjav, Vedran (International journal of project management, 2021)
•Trust dynamics is driven by the interplay of structures and interactions that generate and maintain ontological security•The interplays of structures and interactions occur at individual, project and firm levels of project contexts•To reproduce and develop trust requires consistency between structures and interactions and between multilevel contexts•Consistency can be achieved through top-down management interventions and bottom-up learning processes An increasing number of projects crosses organisational boundaries and inter-organisational trust is key to achieving consistent outcomes among different organisations. While research has demonstrated the relationships between trust and managerial practices in project organisations, the dynamics of trust in project ecologies and the driving force behind dynamics have received little attention in empirical research and require investigation. Analysing the relationship between a project-based firm and its supplier at three project data points and from the perspective of structuration theory, the study showed how trust was reproduced and developed in successive interactions. The findings suggested that the dynamics of trust is driven by the interplay of trust-building structures and interactions that generate and maintain a sense of ontological security in the relationship. Moreover, the interplays of structures and interactions were found at individual, project and firm levels of project contexts. To reproduce and develop trust requires consistency between structures and interactions in multilevel contexts, which can be achieved through top-down management interventions and bottom-up learning processes. The study enriches trust theories in project studies by theoretically and empirically explicating the process of trust reproduction and development and the driving force of trust dynamics in the multilevel project contexts.